Social Media, Power, and the Future of VBAC - Romano, Amy M. (Lamaze International Inc., 2010)
The Internet has been called a disruptive technology because it has shifted power and altered the economics of doing business, whether that business is selling books or providing health care. Social media have accelerated the pace of disruption by enabling interactive information sharing and blurring the lines between the “producers” and “consumers” of knowledge, goods, and services. In the wake of the National Institutes of Health Consensus Development Conference on Vaginal Birth After Cesarean (VBAC) and major national recommendations for maternity care reform, activated, engaged consumers face an unprecedented opportunity to drive meaningful changes in VBAC access and safety. This article examines the role of social networks in informing women about VBAC, producing low-cost, accessible decision aids, and enabling multi-stakeholder collaborations toward workable solutions that remove barriers women face in accessing VBAC.